2021
DOI: 10.1126/sciadv.abe4334
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-driven actin-microtubule networks exhibit self-organized contractile dynamics

Abstract: The cytoskeleton is a dynamic network of proteins, including actin, microtubules, and their associated motor proteins, that enables essential cellular processes such as motility, division, and growth. While actomyosin networks are extensively studied, how interactions between actin and microtubules, ubiquitous in the cytoskeleton, influence actomyosin activity remains an open question. Here, we create a network of co-entangled actin and microtubules driven by myosin II. We combine dynamic differential microsco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 57 publications
1
53
1
Order By: Relevance
“…These dual observations challenge existing theoretical models. They are also different from previous work with myosin-driven MT–actin composites, which showed that the viscoelastic response could be tuned by the addition of a second material component, but the symmetry of the active stress did not change ( 43 ). However, they are broadly consistent with previous experimental work in which the deformations of rigid filaments changed from extensile to contractile through the addition of passive cross-linkers ( 52 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These dual observations challenge existing theoretical models. They are also different from previous work with myosin-driven MT–actin composites, which showed that the viscoelastic response could be tuned by the addition of a second material component, but the symmetry of the active stress did not change ( 43 ). However, they are broadly consistent with previous experimental work in which the deformations of rigid filaments changed from extensile to contractile through the addition of passive cross-linkers ( 52 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our work builds on the previous studies of active composites ( 42 , 43 ). So far, we have described how increasing F-actin concentrations induce transitions from the extensile fluid to layered asters and then, to global contractions.…”
Section: State Diagram Of the Actin–mt Compositesmentioning
confidence: 88%
See 1 more Smart Citation
“…Microtubules are cytoskeletal filaments that permeate the cytoplasm of all eukaryotic cells and play a pivotal role in numerous biological processes, including intracellular transport, cell motility, cell morphology maintenance and formation of mitotic spindle to facilitate chromosome separation during cell division [133][134][135][136][137]. Microtubules are inherently dynamic and capable of organizing and restructuring into different architectures in precise timing and location to facilitate various cellular functions [138,139]. During mitosis, the microtubule dynamics are increased by 20-100-fold [140].…”
Section: Anti-cancer Properties Of Alkaloidsmentioning
confidence: 99%
“…The corresponding correlation length ξ is obtained by curve-fitting autocorrelation curves to g(r) g o exp(−r/ξ). This approach is based on previous studies that have applied SIA to confocal images of cytoskeleton networks to determine correlation lengthscales [58,59]. Because many of the curves exhibit non-exponential tails at large distances due to flat-field noise, as in these prior studies, we restrict curvefitting to g(r ≤ 2 μm).…”
Section: Methodsmentioning
confidence: 99%